Atypical pneumonia caused by Chlamydia psittaci during the COVID-19 pandemic. (September 2022) - Yin, Qiaoqiao; Li, Yuecui; Pan, Hongyi; Hui, Tianchen; Yu, Zhaonan; Wu, Haiyan; Zhang, Dehe; Zheng, Wei; Wang, Shouhao; Zhou, Zhewen; Xu, Chengan; Wu, Wenhao; et al.
Highlights: This study enrolls the highest number of cases of human psittacosis in China Diagnosis and treatment for C. psittaci pneumonia are summarized mNGS is a suitable tool for the diagnosis of pneumonia of unknown cause The detection rate of mNGS is higher than PCR in blood for diagnosing psittacosis Atypical pneumonia may be misdiagnosed or underdiagnosed under the COVID-19 pandemic. Abstract: Objectives: Here, we retrospectively described the diagnosis and treatment of 32 cases diagnosed with Chlamydia psittaci pneumonia during the COVID-19 pandemic. Methods: Clinical information was collected from all the patients. Reverse transcription–PCR and ELISAs were conducted for the detection of COVID-19 using nasal swabs and bronchoalveolar lavage fluid (BALF) samples. Metagenomic next-generation sequencing (mNGS) was performed for the identification of causative pathogens using BALF, peripheral blood and sputum samples. End-point PCR was performed to confirm the mNGS results. Results: All 32 patients showed atypical pneumonia and had infection-like symptoms that were similar to COVID-19. Results of reverse transcription–PCR and ELISAs ruled out COVID-19 infection. mNGS identified C. psittaci as the suspected pathogen in these patients within 48 hours, which was validated by PCR, except for three blood samples. The sequence reads that covered fragments of C. psittaci genome were detected more often in BALF than in sputum or blood samples. All patients received doxycycline-based treatment regimens and showed favorable outcomes. Conclusion: This retrospective study, with the highest number of C. psittaci pneumonia enrolled cases in China so far, suggests that human psittacosis may be underdiagnosed and misdiagnosed clinically, especially in the midst of the COVID-19 pandemic.